Evolución de la Industria de las Telecomunicaciones en Chile - Rodríguez Ariztía, Andrés (2024)
Since the 1980s, Chile has witnessed significant development in its telecommunications industry. From natural monopolies to a complete opening to foreign investment and the advent of new technologies, Chile is now positioned as a regional HUB for emerging technologies, witnessing remarkable transformations in the telco business structure. This article will address the development of the telecommunications industry from two thematic axes: (1) the evolution and regulation of mobile telephony in Chile; and (2) the telecommunications infrastructure in the country. The foregoing aims to expose the main regulatory challenges in these areas identified by both the industry in general and the national regulatory authority, the Subsecretariat of Telecommunications of Chile.